2020
DOI: 10.3390/su12031269
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Networks in Improving International Performance and Competitiveness: Perspective View of Open Innovation

Abstract: With perspective view of open innovation, this study examines how international networks form and evolve and the empirical relationships among antecedents of international network embeddedness, international performance, and sustainable competitiveness. Data from 356 small and medium-sized exporters (SMEs) in manufacturing or technology industries in South Korea are analyzed by structural equation modeling. It assumes that international network embeddedness plays a mediating role in the relationship between in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
(126 reference statements)
0
7
0
2
Order By: Relevance
“…In an industry as globalised as tourism, it can be interesting to create and maintain strong international networks, as they have recently been shown to be a determining factor in improving the export performance of small-and medium-sized enterprises (SMEs) [107].…”
Section: Variables Related To Social Capitalmentioning
confidence: 99%
“…In an industry as globalised as tourism, it can be interesting to create and maintain strong international networks, as they have recently been shown to be a determining factor in improving the export performance of small-and medium-sized enterprises (SMEs) [107].…”
Section: Variables Related To Social Capitalmentioning
confidence: 99%
“…Despite the limited financial, human, and tangible resources that usually characterize small and medium-sized enterprises (SMEs), some of these firms achieve considerable success in international business early in their development [2][3][4]. The acceleration of the internationalization process is shaped by the leverage of firm's resources and capabilities [5,6] and external factors such as institutional environment or innovation networks [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the studies by Santoro et al (2019) stand out, who empirically proved a positive relationship between an external knowledge supply strategy and internationalization in 135 SMEs in Europe. Yoon and Ryu (2020) established that international networks are essential for SMEs because they help establish and intensify and optimize international performance. Ryu, Baek, and Yoon (2021) found that technological innovation capacity significantly influences international performance.…”
Section: Open Innovation and Internationalization In Smesmentioning
confidence: 99%